VdP5CDH is involved in melanin formation, stress resistance and play a regulatory role in virulence of Verticillium dahliae - Sun, Wanqing; Zhao, Lihong; Zhou, Jinglong; Feng, Hongjie; Zhang, Yalin; Feng, Zili; Zhu, Heqin; Wei, Feng (Frontiers in Microbiology, 2024)
V. dahliae, a soil-borne fungal pathogen, can cause cotton Verticillium wilt. In this study, VdP5CDH, the member of the ALDH_F4-17 family of carboxylate dehydrogenases, was identified in the genome of V. dahliae and investigated function in regulating virulence by generating gene deletion mutants and complementary mutants. The conidial surface of VdP5CDH deletion strains was dented and shriveled, and the number of conidial spores increased. Compared with the wild-type (WT), the mycelial diameter of deletion mutants increased by 10.59%-11.16%, the mycelial growth showed irregular branching patterns, and misaligned arrangement. Although capable of penetrating cellophane, deletion mutants were unable to produce melanin. RNA-seq revealed that VdP5CDH was mainly associated with glucose metabolism, nitrogen metabolism, ABC transporter activity as well as various amino acid metabolic processes.After gene knockout, raffinose and pectin were used as the main carbon sources to promote the growth of strains. Raffinose had a certain promotion effect on the growth of each strain, and the growth rate of the deletion strains in the medium containing raffinose was higher than that of WT. Consequently, the deletion mutant strains decreased utilization efficiency with which they utilized various nitrogen sources. The deletion mutants maintain responsiveness to osmotic stress and oxidative stress stimuli.Additionally, compared to WT strains, the deletion mutant strains exhibited differences in culture temperature tolerance, UV exposure response, and fungicide sensitivity.VdP5CDH regulated the production of glutamate in fungi and the spraying of glutamate was used to simulate the effect of glutamate on host plants. After cotton was infected with deletion strains conidial suspension, its disease index increased dramatically, while it gradually decreased after spraying with 2 mM glutamate in batches. With the increase of spraying times, the effect was more significant, and the disease index decreased by 18.95%-19.66% at 26 dpi. These results indicated that VdP5CDH regulates the pathogenicity of fungi and controls mycelia growth, melanin formation, conidia morphology, abiotic stress resistance, and the expression of infecting structure-related genes.